Game-based Learning using Augmented Reality - Li Ying, Ooi; Hipiny, Irwandi; Ujir, Hamimah; Samson Juan, Sarah Flora (2021)
Game-based learning with Augmented Reality (AR) is fast gaining popularity as an educational tool for primary school students due to its proven effectiveness, particularly for lower age groups. The present ubiquity of smart devices also contributes to the rapid adoption of such technology in classrooms. The gamification element and instantaneous feedback are vital to gain and maintain younger students’ focus and interest. This study investigates the effects of using such tool on students’ learning of the Solar system; a topic that is part of the Malaysian upper primary school’s Science syllabus. The study was conducted remotely involving 20 respondents from various public primary schools in Malaysia. Pre-test and post-test results are presented in this paper. The result validates the effectiveness of the developed game-based learning app, i.e., SoLAR Kid, in improving students’ understanding of the topic. From our experiment, we observed a clear mean difference between pre-test and post- test scores.